The Role of Organizational Forgetting and Organizational Culture on Organizational Learning in Electro Industry - Gromyko Bongso; Maruf Akbar; Wibowo Wibowo (Journal of International Conference Proceedings (JICP), 2019)
Electro companies in Indonesia need organizational learning to be able to adapt to changes. The purpose of this study was to determine the influence of forgetting organizations and organizational culture on organizational learning for employees in the electro companies. This study used 205 employees at electro companies in Indonesia. The results show that organization forgetting has a significant and positive effect on organizational learning. Organizational culture also has a significant and positive effect on organizational learning. The implication of this study are expected that electro companies in Indonesia are able to create organizational learning by giving attention to organizational forgetting because it has the higher impact and has become an interesting phenomenon.